Application of ferric-silicon coagulant-flocculant of electric steel smelting slag for leachate treatment of communal solid waste landfills - A. Vasilenko, T; A. Koltun, A (International Journal of Engineering and Technology, 2018)
In the Russian Federation the most common way of disposal of waste products is landfill. One of its drawbacks is the formation of highly contaminated filtration water. It was made an attempt to treat the leachate with a ferric coagulant-flocculant obtained from the electric steel smelting slag after the acid treatment with hydrochloric acid (the modification time of 1.5 N HCl at 40 °C is no more than 1 hour). To improve the treatment efficiency of highly contaminated leachate it was analysed  a simultaneous application of the obtained coagulant-flocculant and conventional coagulants Al(SO4)2 and ferric chloride). It was shown a decrease in the values of the chemical oxygen demand (COD) by 94.4%, the color of the leachate by (91.3%). It was  studied the physical and chemical properties of the filtration waters of the waste disposal landfill, as well as the dependence of the formation of the precipitable sediment volume on the portion of the injected coagulants and flocculant.